ANALISIS IMPLEMENTASI STRATEGI DIGITAL MARKETING DI ERA SOCIETY 5.0 PADA PRODUSEN TAHU BAKSO MAS ARTA - Dinata, Arta Prawira; Istikhoroh, Siti; Lasiyono, Untung (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
In era society 5.0 the development of technology and information is growing very quickly and developing increasingly rapidly. Companies that can compete in the era society 5.0 are companies maximizing the benefits of information technology developments, especially in the product marketing process, digital marketing strategy is one of the most effective strategies. And efficient to carry out the product marketing process. This research aims to determine the implementation of digital marketing strategies in the era of society 5.0 in Mas Arta meatball tofu producers. The research method used is a qualitative method with an interpretive paradigm which aims to gain insight into the digital marketing strategy implemented by the Mas Arta meatball tofu producer in the era of society 5.0. The results of this research are the iImplementation of Digital Marketing Strategy in the Society 5.0 Era at the Mas Arta Bakso Tofu Producer for its consumers referring to the digital marketing marketing mix. There are several components in the digital marketing marketing mix, namely; Product, price, distribution, promotion, so that these components run well, the Mas Arta meatball tofu producer takes an integrated digital marketing approach. This approach is used to answer the implementation of digital marketing strategies in the era of society 5.0 for the Mas Arta meatball tofu producer: Using advertising/ads on the applied platform, Carrying out live/introducing products directly through the social media used, Utilizing content creators as the originator of product marketing.